Do ESG Disclosure and Financial Reporting Quality Improve Firm Value? The Moderating Role of Financial Constraints: Study Between Indonesia and Malaysia - Ardina Nuresa; Fatima, Hanifatul (Universitas Muhammadiyah Malang, 2026)
Purpose: This study aims to investigate the effect of Environmental, Social, and Governance (ESG) disclosure and Financial Reporting Quality (FRQ) on firm value, with Financial Constraint (FC) as a moderating variable. The research focuses on manufacturing companies in Indonesia and Malaysia. Methodology/approach: The study employs panel data analysis using EViews 12 software. The sample consists of publicly listed manufacturing firms from Indonesia and Malaysia. ESG disclosure and FRQ are measured based on secondary data from annual and sustainability reports, while FC serves as the moderating variable to test its conditional impact on the main relationships. Findings: The results indicate that ESG disclosure significantly enhances firm value by fostering investor confidence and strengthening corporate legitimacy. Conversely, FRQ does not directly affect firm value, suggesting that financial transparency alone is insufficient without ethical and sustainable commitments. Furthermore, FC strengthens the relationship between ESG disclosure and firm value, implying that firms maintaining sustainability initiatives under financial constraints are perceived as more resilient and trustworthy. However, FC does not moderate the relationship between FRQ and firm value. Practical implications: The findings highlight the importance for managers and policymakers to integrate transparency and sustainability as complementary strategies for long-term value creation. Companies should not only focus on financial reporting quality but also enhance ESG performance to attract responsible investors and maintain legitimacy in competitive markets. Originality/value: This study contributes to the limited comparative literature on Indonesia and Malaysia by integrating ESG disclosure, financial reporting quality, and financial constraints into a single model. It emphasizes that firm value in the modern era is increasingly shaped by honesty, accountability, and resilience under financial challenges.